2014
DOI: 10.1080/02791072.2014.944290
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Vulnerable Attachment Style, Psychopathology, Drug Abuse, and Retention in Treatment Among Methadone Maintenance Treatment Patients

Abstract: The relationship between vulnerable attachment style, psychopathology, drug abuse, and retention in treatment among patients in methadone maintenance treatment (MMT) was examined by the Vulnerable Attachment Style Questionnaire (VASQ), the Symptom Checklist-90 (SCL-90), and drug abuse urine tests. After six years, retention in treatment and repeated urine test results were studied. Patients with vulnerable attachment style (a high VASQ score) had higher rates of drug abuse and higher psychopathology levels com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…It was more common in the in-patients rather than in the out-patients and in double diagnosis against single diagnosis patients, indicating that this symptom is peculiar to severe addictions. Numerous studies have found associations between addiction disorders and paranoid ideation ( Potik et al, 2014 ; Moss et al, 2015 ; Del Pino-Gutiérrez et al, 2016 ) either in terms of vulnerability ( Potik et al, 2014 ) or in terms of the causal effect of drugs on paranoia symptoms. It has been widely demonstrated that all kind of substances, such as cannabis ( Freeman et al, 2014 ) cocaine ( Roncero et al, 2014 ), methamphetamine ( Kalayasiri et al, 2014 ), and alcohol ( Bouzyk-Szutkiewicz et al, 2012 ), induce paranoid ideation.…”
Section: Discussionmentioning
confidence: 99%
“…It was more common in the in-patients rather than in the out-patients and in double diagnosis against single diagnosis patients, indicating that this symptom is peculiar to severe addictions. Numerous studies have found associations between addiction disorders and paranoid ideation ( Potik et al, 2014 ; Moss et al, 2015 ; Del Pino-Gutiérrez et al, 2016 ) either in terms of vulnerability ( Potik et al, 2014 ) or in terms of the causal effect of drugs on paranoia symptoms. It has been widely demonstrated that all kind of substances, such as cannabis ( Freeman et al, 2014 ) cocaine ( Roncero et al, 2014 ), methamphetamine ( Kalayasiri et al, 2014 ), and alcohol ( Bouzyk-Szutkiewicz et al, 2012 ), induce paranoid ideation.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies (15/18, 83%) had clear information on diagnoses of mental disorders or mental health concerns. 20,[24][25][26][27][28][29][30][31][32][33][34][35][36][37] The remaining 3 articles used a broad definition of mental health (e.g., 'a mental health concern') 38,39 or enrolled individuals following a suicide attempt and/or potentially traumatic event. 40 Ten different questionnaires/ scales were used to measure attachment.…”
Section: Resultsmentioning
confidence: 99%
“…Their classification included 8 studies on treatment engagement, 25,26,28,31,35,[37][38][39] 4 studies on treatment participation, 20,31,34,40 and 7 studies on treatment completion. 24,27,29,30,32,33,36 The research findings are summarized below according to the specific treatment utilization category researched.…”
Section: Resultsmentioning
confidence: 99%
“…In brief, each patient drinks the individual methadone dosage every day in the clinic and is encouraged to earn the privilege to receive " take home " dosages of medication (for up to 2 weeks) if they stop illicit drug use and present acceptable behaviour. Patients attend regular personal psychosocial therapy appointments with specialized counsellors (Potik et al 2007(Potik et al , 2014Abramsohn et al 2009). Patients also participate in several therapy groups (i.e., a mandatory seminar for newly admitted patients) and may participate in psychiatric diagnoses, and it was 16.4 years (95% CI 15.9 -16.9) for all patients.…”
Section: Clinicmentioning
confidence: 99%